A Novel Displacement-amplifying Compliant Mechanism Implemented on a Modified Capacitive Accelerometer - Ramon Cabello-Ruiz; Margarita Tecpoyotl-Torres; Alfonso Torres-Jacome; Volodymyr Grimalsky; Jose Gerardo Vera-Dimas; Pedro Vargas-Chable (Institute of Advanced Engineering and Science, 2017)
The micro-accelerometers are devices used to measure acceleration. They are implemented in applications such as tilt-control in spacecraft, inertial navigation, oil exploration, etc. These applications require high operating frequency and displacement sensitivity. But getting both high parameter values at the same time is difficult, because there are physical relationships, for each one, where the mass is involved. When the mass is reduced, the operating frequency is high, but the displacement sensitivity decreases and vice versa. The implementation of Displacement-amplifying Compliant Mechanism (DaCM) supports to this dependence decreases. In this paper the displacement sensitivity and operation frequency of a Conventional Capacitive Accelerometer are shown (CCA). A Capacitive Accelerometer with Extended Beams (CAEB) is also presented, which improves displacement sensitivity compared with CCA, and finally the implementation of DACM´s in the aforementioned devices was also carried out. All analyzed cases were developed considering the in-plane mode. The Matlab code used to calculate displacement sensitivity and operating frequency relationship is given in Appendix A.